Modification of District Integrated Administrative Services (PATEN) and Super Service Delivery Models at Polewali Mandar - Sitti Chaeriah Ahsan; Risma Niswaty; Irsyad Dhahri (Iapa Proceedings Conference, 2021)
In order to realize the demands of the community in service, the government will seek several things to improve the quality of services provided by bringing up a policy. To produce a quality policy requires good cooperation by the local government. Improving public services to optimize services in the regions can be done by reforming the administration at a level that is directly dealing with the community, namely at the sub-district level and implementing innovation. The innovation in question is the sub-district integrated administrative service system (PATEN). PATEN is held with the aim of realizing the sub-district as a community service center and becoming a service node for the one-stop integrated service agency/office (PTSP) in the district for sub-districts whose geographical area will be more effectively and efficiently served through the sub-district. With a qualitative method, this research on the implementation of PATEN in Polewali Mandar was studied based on the concepts of communication, resources, disposition, and bureaucratic structure. Obstacles encountered in communication due to limitations in providing patent services to the public during the covid 19 pandemic, PATEN service providers were provided with training, related to disposition, clearer supervision standards were needed regarding the use and supervision of budgets by districts so that achievements and obstacles could be evaluated on a regular basis ; and simplification of standard operating procedures on aspects of bureaucratic structure.